SOME PROBLEMS OF THE ORGANIZATION OF NETWORK INTERUNIVERSITY INTERACTION - E. K. GITMAN; M. B. GITMAN; V. Yu. STOLBOV; A. P. CHUGUNOV (Высшее образование в России)
The article addresses the problems of network interaction organization in Russian higher education system. The problems are divided into several groups: organizational, methodical, and concerning the informational basis and individualization of student study process. Prospective solutions of the problems for Russian universities are provided too. Solutions are based on network education program being developed in module and competence form and individual education program constructed with the preference to student wishes. Problems of organization of network interaction with foreign universities are considered separately. There are also offered the prospective approaches to international education program realization. One of them can be teaching of interesting for foreign students modules in English or their additional training in learning Russian.